An Analysis of Cohesive Reference in English Scientific Texts Translated into Arabic - Ash-Sharki, Aisha; Ashuja'a, Abdulhameed (University of Science and Technology Journal for Management and Human Sciences, 2025)
This study examined the similarities and differences in the frequency and use of cohesive reference in English scientific abstracts and their Arabic translations. A quantitative method was employed by developing and applying a checklist based on Halliday and Hasan’s (1976) model for evaluating cohesive reference: (personal pronoun, demonstrative reference and comparative reference).  A corpus of 31 English research abstracts with their Arabic translations was selected from four academic journals. The findings revealed a higher frequency of references in English (421) than Arabic (332), which was attributed to the application of reduction and compensation strategies in translation, thereby decreasing the number of cohesive devices in Arabic. Nevertheless, both languages followed a similar frequency order of cohesive devices: demonstrative references were the most prevalent (339 and 259 in English and Arabic respectively), reflecting the clarity, transparency, and precision of scientific texts. Personal pronouns and comparative references ranked second and third, respectively. The study underscored the necessity for translators and student-translators to develop an in-depth understanding of cohesion, particularly cohesive reference, in English and Arabic. It further recommended the inclusion of cohesion-focused content in translation curricula to equip student-translators with the knowledge and skills to select and apply appropriate strategies for specific contexts.
Keywords: cohesion; cohesive reference; anaphoric; cataphoric; exophoric